2020
DOI: 10.1186/s13756-020-00768-9
|View full text |Cite
|
Sign up to set email alerts
|

A population-base survey on knowledge, attitude and awareness of the general public on antibiotic use and resistance

Abstract: Objectives: This study was designed to assess the awareness and knowledge of antibiotic usage and antibiotic resistance among the general public in the Cape Coast metropolis of Ghana. It also tries to decipher whether the level of education and the professional status of an individual has a positive association with the level of knowledge on antibiotic resistance. Methods: A population-base survey involving members of the public was conducted from August to November 2019. A structured questionnaire was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 28 publications
5
28
2
4
Order By: Relevance
“…Also, about 75% respondents are not aware that antibiotics can negatively alter our own natural bacterial flora. This finding are correlates with various past studies studies [22,11,12,13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, about 75% respondents are not aware that antibiotics can negatively alter our own natural bacterial flora. This finding are correlates with various past studies studies [22,11,12,13].…”
Section: Discussionsupporting
confidence: 93%
“…Patients aged 18 years or above were included in study. Well-structured questionnaires were prepared in English and official regional language Marathi.The questionnaires mostly based on the questions taken from various previous studies, which were edited in context with the objectives of the study [11,12,13]. A literature review of past similar studies of antibiotics misuse was done to identify potential domains for the study instrument and changes made to suit the local population.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Almost two-thirds (62.6%) of those surveyed had adequate health literacy, which is slightly higher than the 57.2% previously reported in a cross-sectional study on the impact of health literacy on self-medication practice [ 25 ]. In line with earlier research [ 16 , 35 ], the findings of this study showed that health literacy levels were comparable across groups, with the exception of the education levels, which had a substantial effect on health literacy. This finding implies that higher education levels provide more broad exposure to antibiotic and health-behavior-related information.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous research, approximately half of those surveyed in this study indicated that pharmacies are their primary source of self-medicated antibiotics [13,26,44]. While pharmacists are responsible for promoting safe and cost-effective drug use, the study findings support previous research emphasizing the pharmacist's role in referring patients with infectious diseases to physicians, advocating for prudent antibiotic use, and preventing antimicrobial resistance [13,35,45].…”
Section: The Use Of Antibioticssupporting
confidence: 88%
“…They used those antibiotics for the treatment of mostly cold 50.8%, cough/chest pain 33.1%, stomach ache 16.9% and skin infection 9.2% 5 . In current study most of the students (64.1%) knew that antibiotic works against bacteria but other answers weren't satisfactory 9 . But the positive sign was that selfmedication of antibiotic was markedly less (2.1%).…”
Section: Discussionmentioning
confidence: 54%